Application of the Saint-Venant Model for Simulation of the Kapuas River Flow Using the Finite Difference Method - Dian Eka Ratnasari; Meliana Pasaribu; Yudhi Yudhi (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2026)
The Kapuas River plays an essential role in transportation, fisheries, tourism, and natural drainage in Pontianak, where river geometry and downstream effects shape its flow conditions. These forces produce variations in discharge and water level over space and time, which can exceed the river’s capacity and cause flooding. This study simulates the dynamics of discharge and water level along the Kapuas Kecil River segment. Researchers developed a mathematical flow model using the Saint-Venant framework, based on mass and momentum conservation principles. This study numerically solved the equations using a finite difference approach with a forward-time and central-space scheme. Researchers collected river width and depth data along a 5 km stretch from Pontianak Utara to Jungkat. The study presents simulation results as spatial and temporal profiles of water level and discharge. The results of this study show that water discharge increases along the channel, while water levels generally decrease over time in the direction of flow. These results provide insights into -influenced river flows in urban environments and can support flood-related analysis and management efforts.